Angle of Arrival Estimation Via Small IoT Devices: Miniaturized Arrays vs MIMO Antennas - Zandamela, Abel Abdul; Narbudowicz, Adam (My University, 2022)
This tutorial discusses the problem of Angle-of-Arrival (AoA) estimation from small Internet of Things (IoT) devices. It reviews the limitations and challenges of existing miniaturization strategies, which involve classical antenna arrays. As larger distance between antennas is typically needed for increased precision, the miniaturization without loss of accuracy is a significant problem. The article demonstrates that the use of electrically small antennas does not directly solve the problem, since smaller antennas may require increased distance to avoid coupling between elements. Therefore, this work proposes a new technique to perform AoA estimation in small platforms – a Multiple-Input Multiple- Output (MIMO) antenna. MIMO antennas are commonly used to increase the communication throughput, however few works have studied their usage for AoA estimation in line-of-sight environment. The proposed solution offers performance similar to state-of-the-art arrays, however at a substantially reduced size. Performance study is carried out to confirm and validate the proposed technique accuracy and miniaturization efficacy. Size reduction up to 75% compared to linear arrays is achieved with mean absolute errors smaller than 0.11°. The method also demonstrates a resolution of 5° with peak mean absolute error of 0.3° for two simultaneous impinging signals.
PUBLISHED
Keywords: Angle of Arrival Estimation; Localization Techniques; Internet of Things; MUSIC algorithm; Small IoT Devices; Compact Antennas; MIMO Antennas; Array Antennas; Multimode Antennas; Telecommunications; Angle of Arrival Estimation; Compact Antennas; Localization; MIMO Antennas; Small Internet of Things; Communication